The mosquito microbiome includes habitat-specific but rare symbionts - Schrieke, Hans; Maignien, Lois; Florentin Constancias; Trigodet, Florian; Chakloute, Sarah; Rakotoarivony, Ignace; Albane Marie; L'ambert, Gregory; Makoundou, Patrick; Pages, Nonito; Eren, A Murat; Weill, Mylene; et al. (bioRxiv, 2021)
Microbial communities are known to influence mosquito lifestyles by modifying essential metabolic and behavioral processes that affect reproduction, development, immunity, digestion, egg survival, and ability to transmit pathogens. Many studies have used 16S rRNA gene amplicons to characterize mosquito microbiota and investigate factors that influence host-microbiota dynamics. However, a relatively low taxonomic resolution due to clustering methods based on arbitrary threshold and the overall dominance of Wolbachia or Asaia populations obscured the investigation of rare members of mosquito microbiota in previous studies. Here, we used high resolution Shannon entropy-based oligotyping approaches to analyze the microbiota of Culex pipiens, Culex quinquefasciatus and Aedes individuals from continental and overseas regions in Southern France and Guadeloupe as well as from laboratories with or without antibiotics treatment. Our experimental design that resulted in a series of mosquito samples with a gradient of Wolbachia density and relative abundance along with high-resolution analyses of amplicon sequences enabled the recovery of a robust signal from typically less accessible bacterial taxa. Our data confirm species-specific mosquito-bacteria associations with geography as a primary factor that influences bacterial community structure. But interestingly, they also reveal co-occurring symbiotic bacterial variants within single individuals for both Elizabethkingia and Erwinia genera, distinct and specific Asaia and Chryseobacterium in continental and overseas territories and a putative rare Wolbachia variant. Overall, our study reveals the presence of previously-overlooked microdiversity and multiple closely related symbiotic strains within mosquito individuals with a remarkable habitat-specificity. Competing Interest Statement The authors have declared no competing interest.